2010
DOI: 10.1186/1471-2164-11-585
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and striatal gene networks: focus on the heterogeneous stock-collaborative cross (HS-CC) mouse

Abstract: BackgroundThe current study focused on the extent genetic diversity within a species (Mus musculus) affects gene co-expression network structure. To examine this issue, we have created a new mouse resource, a heterogeneous stock (HS) formed from the same eight inbred strains that have been used to create the collaborative cross (CC). The eight inbred strains capture > 90% of the genetic diversity available within the species. For contrast with the HS-CC, a C57BL/6J (B6) × DBA/2J (D2) F2 intercross and the HS4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 61 publications
(83 reference statements)
5
78
0
Order By: Relevance
“…An analysis of a commercial outbred stock, presented in a G3 article by W. Zhang et al, underscores the lack of genetic diversity in current mouse stocks that motivated the creation of the CC and DO populations (2012). Data presented in these articles confirm and extend the power of a previous heterogeneous stock also developed from the CC founders (Iancu et al 2010).…”
Section: Collaborative Cross Presentsupporting
confidence: 67%
“…An analysis of a commercial outbred stock, presented in a G3 article by W. Zhang et al, underscores the lack of genetic diversity in current mouse stocks that motivated the creation of the CC and DO populations (2012). Data presented in these articles confirm and extend the power of a previous heterogeneous stock also developed from the CC founders (Iancu et al 2010).…”
Section: Collaborative Cross Presentsupporting
confidence: 67%
“…While these resources have enabled substantial progress in the understanding of mechanisms underlying the effects of addictive drugs, each has some limitations in power, precision, genetic diversity, and genetic architecture. The Collaborative Cross inbred strains (CC), DO mouse population, and related populations (Ghazalpour et al 2012; Iancu et al 2010) complement these resources with a wealth of allelic variation, high mapping precision and a greater range of behavioral diversity (reviewed in Chesler 2014). Allelic variants can be identified using a QTL mapping approach in combination with functional genomic data resources (Recla et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Central administration of NPY or a selective NPY Y1 receptor agonist reduces intake and BEC in the DID test in B6 mice [15], and a similar effect has been seen with NPY Y1 receptor activation in the bed nucleus of the stria terminalis (BNST) [22]. In the HDID mice, gene network connectivity analysis of striatal tissue from naïve mice of both selection replicates and unselected heterogeneous stock (HS) mice found selection-dependent alteration of connectivity of the gene encoding the NPY Y2 receptor [20]. A microarray study measuring NPY mRNA in naïve HDID- 1 and HS mice showed greater Npy gene expression in the NAc, CeA, and BNST of HDID-1 mice than HS mice [23].…”
Section: Introductionmentioning
confidence: 96%
“…However, continuous access preference drinking may only result in limited experience of intoxicating BECs and might not always reflect consumption that is driven by the pharmacological effects of ethanol [19]. Continuous access preference drinking and limited access DID are also believed to be genetically distinct traits [20][21]. Therefore, investigating the neurobiological factors relevant to DID binge-like drinking is useful for fully understanding drinking to intoxication.…”
Section: Introductionmentioning
confidence: 99%